THE STUDY OF COCKROACH ALLERGY IN IRANIAN CHILDREN WITH ASTHMA - A. Farhoudi; Z. Pourpak; M. Mesdaghi; A. Kazemnejad Z. Chavoshzadeh (Acta Medica Iranica, 2003)
Asthma is the most common chronic disease of childhood. Exposure to allergens plays an important role in asthma. Recently, cockroach has attracted attentions as an important allergen. This study was performed to evaluate cockroach allergy in Iranian children with asthma. One hundred children with definite diagnosis of asthma were selected. After obtaining primary information, the severity of their disease was determined according to their history, physical exam and measurement of PEFR (Peak Expiratory Flow Rate) with a mini peakflowmeter. Also, serum total IgE and blood eosinophil count were measured. The patients were skin prick tested with cockroach (Blattella germanica), trees, weeds, grasses, cats, mite, feather and common food allergens. According to cockroach skin prick test (SPT) results, the patients were divided into two groups (sensitive and non‑sensitive) and compared. Positive SPT for cockroach was detected in 29% of patients. Cockroach sensitive group had a more severe asthma than non-sensitives (P